Azulenophenanthrenes from 2, 2′‐Di(arylethynyl)biphenyls through CC Bond Cleavage of a Benzene Ring1. Issue 25 (6th May 2013) - Matsuda, Takanori; Goya, Tsuyoshi; Liu, Lantao; Sakurai, Yusuke; Watanuki, Shoichi; Ishida, Naoki; Murakami, Masahiro
<x xml:space="preserve">Abstract</x> From six to seven: 2, 2′‐Di(arylethynyl)biphenyls undergo a skeletal rearrangement in the presence of a platinum(II) catalyst to afford polycyclic aromatic compounds containing an azulene unit. The reaction involves CC bond cleavage of a benzene ring, which expands into a seven‐membered ring.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>